Pemotongan Gaji Karyawan Sebagai Ganti Rugi Barang Hilang Perspektif Wahbah Az-Zuhayli (Study Kasus Alfamart Batang Beruh Kabupaten Dairi) - Ramidah Situmorang, Anggi; Zuhri, Ahmad (Dinasti Review Publisher, 2024)
In fiqh muamalah, wages are compensation received by a worker for the benefits of work that he has done properly and correctly in the form of material rewards in the world (fair and decent). However, it is different from what happened at Alfamart Batang Beruh where the monthly salary is given after first deducting NBH unfairly. The case of employee wage deductions is very worrying because these deductions are made as compensation for lost goods, The object of research is focused on the practice of applying compensation for lost goods notes (NBH) to employee wages (salaries), at Alfamart Batang Beruh Dairi Regency Wahbah Az-Zuhayli Perspective, This research is empirical research, where researchers try to describe and analyze these practices using a normative approach, with reference to Wahbah Az-Zuhayli's opinion. Data collection by going directly to the field through observation, and free question and answer (interview). While in analyzing the data, researchers used descriptive analysis. This study concludes that the practice of deducting employee wages as compensation for lost goods notes at Alfamart Batang Beruh, Dairi Regency, is invalid, because it is not in accordance with the theory of ij?rah, which violates the